Digital Readiness in Islamic Education: A Case Study of Pesantren Assalafiyyah Mlangi Sleman, Indonesia - Ahmad Zuhdan Makhluf; Nazila Khoerunnisa; Siti Nur Rondiyah; Umun Mu'aimanah (Journal of Islamic Education Management Research, 2023)
Purpose – The study's primary objective was to assess the level of preparedness among students at Pondok Pesantren Assalafiyyah Mlangi, Komplek Kitab Putra Madrasi, in navigating the challenges of the digital era, with a specific focus on their adaptability within the sphere of Islamic education. Design/methods– A quantitative research methodology was adopted, centering on a survey conducted among 302 active male students at the institution. The sample size, which amounted to 75 students, was calculated using the Solvin formula. A structured questionnaire, designed to evaluate various aspects of digital literacy and adaptability, was employed for data collection, with the analysis executed through Likert scale scoring. Findings – The study unveiled a substantial level of digital literacy among the students. It was found that the majority of students had access to digital devices and were capable of discerning between positive and negative content on the internet. Notably, 84% of the survey responses were classified as 'Highly Suitable' in terms of digital era readiness, based on Arikunto's evaluative scale. Research implications/limitations – These findings indicate an imperative need to deepen the integration of digital literacy and ethical considerations within Islamic educational curricula. However, the research's confinement to a single educational institution poses limitations on the broader applicability and generalizability of its conclusions. Practical implications – The results emphasize the importance of incorporating comprehensive digital education in Islamic educational settings, preparing students not only for technological proficiency but also for responsible and ethical digital engagement. Originality/value – This study contributes valuable insights into the current state of digital readiness among students in an Islamic educational context. Its focus on the intersection of traditional Islamic education with contemporary digital challenges presents a unique perspective in educational research.